Um framework de rastreamento corporal para reabilitação neuromotora com suporte a aplicativos multimídia - Ribeiro, Elvis; Brandão, Alexandre; Guimarães, Marcelo; Rocha, Leonardo; Brega, José Remo; Dias, Diego (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the Web, 2024)
Multimedia applications and games play a crucial role in rehabilitation and health, providing an interactive and engaging approach that can improve patient motivation, facilitate progress monitoring, and personalize treatment plans. They offer an innovative physical and cognitive therapy platform, allowing healthcare professionals to explore new forms of treatment and patients to experience a more enjoyable and effective recovery. Despite recent advances in hardware and software, integrated solutions still need to be developed to facilitate the development of new applications, especially those that use body-tracking sensors. This paper presents the framework for a development solution that simplifies the creation of new natural user interface (NUI) applications based on inertial sensors, supporting both tracking and the creation of sessions and data storage. We also present examples of applications developed to show the potential of the solution for developing new applications that use the user’s own body as a means of interaction.